(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Let be a graph. Let be a group. For let denotes the order of in Let be a function. For eachedge assign the label Let denote the number of vertices of having label under Alsorespectively denote the number of edges labeled withand not with .Nowis called a group difference cordial labeling if for every and . A graph which admits a group difference cordial labeling is called group difference cordial graph. In this paper we fix the groupas the group which is the group of fourth roots of unity, that is cyclic with generators We prove that Open ladder, Slanting ladder and further characterized .